2019
DOI: 10.1016/j.rse.2019.111442
|View full text |Cite
|
Sign up to set email alerts
|

Recent evolution of Marmolada glacier (Dolomites, Italy) by means of ground and airborne GPR surveys

Abstract: A 10-year-long evolution of ice thickness and volume of the Marmolada glacier is presented.Quantitative measurements have been performed by using two different Ground Penetrating Radar (GPR) datasets. A ground-based survey using two different ground-coupled systems equipped with 100 MHz and 35 MHz antennas was performed in 2004. In 2015 the dataset was collected by using a helicopter-borne step frequency GPR equipped with a 100 MHz antenna. Through a critical discussion of the two different methodologies, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 75 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…Christian et al 2018) and part of their future mass loss is committed even without further warming (e.g. Bahr et al 2009;Mernild et al 2013;Marzeion et al 2017Marzeion et al , 2018Santin et al 2019). In 2001, the committed volume loss was 34% of the total ice volume at that time, increasing to 42% in 2010 (Zekollari et al 2020).…”
Section: Implications For Future Glacier Statementioning
confidence: 99%
“…Christian et al 2018) and part of their future mass loss is committed even without further warming (e.g. Bahr et al 2009;Mernild et al 2013;Marzeion et al 2017Marzeion et al , 2018Santin et al 2019). In 2001, the committed volume loss was 34% of the total ice volume at that time, increasing to 42% in 2010 (Zekollari et al 2020).…”
Section: Implications For Future Glacier Statementioning
confidence: 99%
“…Some studies (Triglav Čekada and Gabrovec 2013; Scotti and Brardinoni 2018;Santin et al 2019) confirm that the smaller is one glacier, the least dependent is it from climate change. Many glaciers in the southern and the eastern Alps have shrunk rapidly throughout the twentieth century, and, when they reached sufficiently small size (e.g.…”
Section: Regional Correlations Of Holocene Glaciation On the Balkansmentioning
confidence: 98%
“…In Prokletije, the rapid shrinkage probably occurred also throughout the last century. At other small glaciers of the Southern Alps (Eiskar, Austria, Marmolada, Italy) the rapid reduction is still in progress (Santin et al 2019;Hohenwarter 2013). Evidence has shown that the glacierets in Pirin were in the "small size" stage also in the LIA, and this provides an explanation why they have changed relatively little since.…”
Section: Regional Correlations Of Holocene Glaciation On the Balkansmentioning
confidence: 99%
“…The main elements of the communication process derive from the models of Shannon (1948) and Berlo (1960). The main elements are the sender (the person transmitting the message), the receiver (the person receiving the message), the message (the communication subject), the channel (the communication vehicle), and the context (where, how, and when the message is sent).…”
Section: Visual Communication and The Exhibitionmentioning
confidence: 99%
“…However, we can hypothesize that, at least in some cases, the combined action of the temperature increase and precipitation decrease that occurred after 1980 influenced the evolution of glaciers. According to the present rate of glacier decline, and according to the observed climatic warming trends, the glaciers in the Italian Alps are expected to disappear by 2050 (Santin et al, 2019).…”
Section: The Alpsmentioning
confidence: 99%